Primary care-based link workers providing social prescribing to improve health and social care outcomes for people with multimorbidity in socially deprived areas (the LinkMM trial): Pilot study for a pragmatic randomised controlled trial - Kiely, Bridget (J Comorb, 2021)
INTRODUCTION: Individuals with multimorbidity in deprived areas experience worse health outcomes and fragmented care. Research suggests that primary care-based link workers providing social prescribing have potential to improve health and well-being. This paper reports the results of a pilot study conducted in preparation for a randomised controlled trial (RCT) that aims to test the effectiveness of primary care-based link workers providing social prescribing in improving health outcomes for people with multimorbidity who attend general practices in deprived areas in Ireland. METHODS: An uncontrolled pilot study of an intervention based on the Glasgow Deep End links worker programme, in a single general practice, tested the feasibility and acceptability of planned processes for a RCT. Outcomes were recruitment and retention rates and acceptability of the trial processes and intervention to patients, general practitioners (GPs) and the link worker. Structured interviews were conducted with six patients, the link worker and two GPs within the practice and analysed using descriptive qualitative analysis. Feedback from a Public Patient Involvement group and an Implementation Advisory Group of key stakeholders was incorporated into the evaluation process. RESULTS: Twelve out of 14 patients completed the intervention. Selection and recruitment processes were lengthier than expected. GPs recommended including psychosocial need in the selection process. Interviewed patients, the GPs and the link worker were positive about the intervention. CONCLUSION: A range of adaptations were identified for the main trial, mainly considering psychosocial need in the selection process to reflect normal referral pathways. This has resulted in a pragmatic RCT design.